Projectivity and flatness over the endomorphism ring of a finitely generated module - S. Caenepeel; T. Guédénon (International Journal of Mathematics and Mathematical Sciences)
Let A be a ring and Λ a finitely generated A-module. We give necessary and sufficient conditions for projectivity and flatness of a module over the endomorphism ring of Λ.